Vapor-liquid solid mechanism using gold colloids for the growth of GaAs nanowires - Muhammad, Rosnita (Ibnu Sina Institute for Fundamental Science Studies, Universiti Teknologi Malaysia, 2008)
GaAs nanowires were grown on the semi insulating undoped GaAs (111)B wafer by using metal organic chemical vapor deposition, MOCVD. The growth follows the vapor-liquid-solid method by applying nanoparticle gold colloid as a catalyst to forms a eutectic liquid alloy with the wafer substrate. The GaAs wafer were first dipped in the poly-L-lysine solution before 30nm gold colloid dropped on the wafer surface. The temperature growth was set at 420 ºC and the growth processes were done between 10 to 60 min. The samples structural were characterized using field emmission scanning electron microscope, FE-SEM and shows the GaAs nanowires height increased with the increasing growth time. On the top of each wire contain ball which include some quantity of Au when anlyze using energy disperve x-ray spectroscopy, EDX